Beggars cannot be choosers : labor market tightness and hiring standards, wages, and hiring costs - Linckh, Carolin [Verfasser]; Mühlemann, Samuel [Verfasser]; Harald Pfeifer [Verfasser] (My University, 2024)
„This study analyzes how firms adjust their hiring practices when labor markets become tighter. Using unique linked employer-employee data for Germany, we find that pre-match search costs represent only 16 percent of total hiring expenditures, while post-match costs account for the remaining 84 percent. We find no evidence of firms raising entry wages in response to labor market tightness, instead they adjust them along two margins. First, in tighter labor markets, firms hire workers whose general ability is lower relative to their existing workforce. Second, they incur higher post-match hiring costs. A one standard deviation increase in labor market tightness is associated with a 0.1 standard deviation de crease in hiring standards, a 10 percent longer adaptation period, and 12 percent higher informal training hours for new hires. These findings reveal an alternative adjustment mechanism that may reflect firms’ wage-setting power, with firms substituting costly post-hire training investments for wage competition.” (authors’ abstract; BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; S 3.2 Unternehmen und Behörden; G 1.2.2.1 Lohn- & Tarifsysteme; 370; 330; Arbeitsmarkt; Unternehmen; Personalgewinnung; Stellenbesetzung; Lohn